The Legal Aspect of Cancellation of a Marriage Due To Formed Identity (Case of Decision Number 586 / PDT.G / 2014 / PN. JAKSEL) - Riki Afri Rizki; Sriono Sriono; Risdalina Risdalina (Budapest International Research and Critics University, 2021)
This article examines the legal aspects of the cancellation of marriage due to identity forgery based on the case of the South Jakarta District Court Decision Number 586 / PDT.G / 2014 / PN.JAKEL , this is regulated in Law number 1 of 1974 concerning Marriage. This research uses normative juridical research, which refers to the provisions of positive laws and regulations in Indonesia among the laws and regulations on Marriage by knowing the procedures of the marriage law and making it a guide in resolving problems in society. The results of the study found indicators of legal aspects between husband and wife that arise because of marriage between them. AThere are different nationalities, so that it becomes a study of International Civil Law and mixed marriage problems in Indonesia between Jessica Iskandar and Ludwig Frans Willibald regarding the validity of the marriage certificate so that it can be canceled and legal consequences after marriage cancellation. So there are important things that need to be considered if there is someone foreigners or non-citizens of Indonesian citizens who will conduct a mixed marriage with an Indonesian citizen. The marriage procedure is regulated in the Implementation Regulation of the Marriage Law, namely Government Regulation No. 9 of 1975 So that there are important things that need to be considered in the applicable marriage law, it should be known about the legal aspects and legal consequences according to the legal aspects in Indonesia.